AN ADVENTURE IN THEORY IN SPECIAL EDUCATION - Benoit, Paul; Gauthier, Yvon (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1983)
Whether those in any helping profession harden their hearts against their clients or empathize with them, they are apt not to think about them as much as they should. For both are emotional habits, tending, if not controlled, to inhibit rational insight and treatment. Benoit and Gauthier plead with eloquence, and a large compassion, for a greater degree of professionalism and intellectual enterprise among those conducting the special education of the retarded; and they offer a review of former theories and Benoit’s own adaptation of a modem one (of Hebb’s), together with a new definition of mental retardation, with the object of stimulating a greater creativity in the practice of that absorbing branch of the profession. RÉSUMÉ Que ceux qui ont pour profession d’aider les autres s’endurcissent le coeur face à leurs clients, ou sympathisent avec eux, il est fort probable qu’ils ne pensent pas à eux autant qu’ils le devraient. Car ces deux sentiments sont des habitudes affectives qui tendent, si elles ne sont pas maîtrisées, à entraver la compréhension et le traitement rationnels. Benoît et Gauthier plaident avec éloquence et beaucoup de compassion en faveur d’un niveau de professionnalisme et d’initiative intellectuelle plus élevés parmi ceux qui assurent l’enseignement des arriérés, et ils présentent une analyse des théories antérieures parallèlement à la propre adaptation de Benoît d’une théorie moderne (celle de Hebb) ainsi qu’une nouvelle définition de l’arriération mentale, dans le but de stimuler une plus profonde créativité dans l’exercise de cette branche très prenante de la profession d’enseignant.